The effect of green betel leave extract (Piper betlel) in feed as prevention of Edwardsiella ictaluri bacterial infection in catfish (Pangasianodon hypopthalmus) - Safratilofa Safratilofa; Syahrizal Syahrizal; Edy Barkat Kholidin; Khairul Amsar Sardani (Universitas Muhammadiyah Malang, 2022)
This study aimed to determine the effect of adding green betel leaf extract to feed on the prevention of Edwardsiella ictaluri bacterial infection in catfish. Betel leaf extract was sprayed into the feed according to the research dose, namely Treatment A pelleted feed + 0.3 mL betel leaf extract / 100 g of feed + injected with E. ictaluri bacteria. Treatment B pelleted feed + 0.6 mL of betel leaf extract/ 100 g of feed + injected with E. ictaluri bacteria. Treatment C pelleted feed + 0, 9 mL betel leaf extract / 100 g feed + injected E. ictaluri bacteria control (+) feed pellet + injected E. ictaluri bacteria control (-) pelleted feed + injected with physiological solution of NaCl 0, 9%. Feeding was carried out for 14 days, the challenge test was carried out on the 16th day, for observation of clinical symptoms, and survival rates were observed for 10 days after the challenge test. The results of the study showed that the best survival rate was in treatment C (66.66%) and the lowest was in treatment A (53.33%) with fewer external and internal clinical symptoms among other treatments.